The essence of software startup : an empirical study on the application of essence framework - Ravaska, Ville (2020)
Software startups are still a scarcely studied subject even though success stories of the companies like Facebook and Twitter have boosted the popularity of new software startup companies. The impact of successful startups for the economy is massive by creation of new jobs and wealth. The Essence framework is relatively new approach for modelling software development in the companies. It has not been extensively tested in the unique case of software startups. Software startup practices have been studied and acknowledged in the academia but further research is still needed to comprehensively understand how these companies work and conduct their work. This thesis studied software startup practices regarding software development and other vital activities performed by these companies. The Essence framework was also introduced to software startups’ working practices. The basis of the thesis was the list of software startup practices derived from previous studies that was categorized following the alphas of the Essence framework. The empirical study was conducted as a multiple case study with thirteen different cases. Three new alphas (funding, marketing and business model) were suggest-ed to the Essence in order to revise the framework to support software startups whole endeavour. Thirteen additional practices were also found from the empirical material. The Essence was found to support software startups software development efforts but lacking the business aspects that cannot be separated from the software development in small new companies working with limited resources.